Academic interest determines the academic performance of undergraduate accounting students: Multinomial logit evidence - Agoestina Mappadang; Khusaini Khusaini; Melan Sinaga; Elizabeth Elizabeth (Cogent Business & Management, 2022)
Academic performance is important for students as a result of educational experience in colleges to represent knowledge, skills, and attitudes. Academic performance becomes one of the key factors in determining students' success in their future careers. This research aimed to assess student's academic interest, learning attitude, and learning quality as well as control variables for the academic performance improvement of undergraduate students in Indonesia. This research employed a cross-section survey design to 872 samples gained by disproportionate random sampling. The research instruments were tested for their validity and reliability. The multinomial logit regression model was employed to analyze academic performance. The results of the research showed that academic interest was proved to determine significantly the academic performance. However, the learning attitude and learning quality did not contribute to the student's academic performance. High academic interest students possessed a bigger chance to have better academic performance. Meanwhile, learning attitude and learning quality indicated otherwise, decrease the students' academic performance. The results of this study contributed to the universities' management to manage innovative and learning activities to promote accounting students' academic interest in continuing better learning. The universities' leaders should fulfill the infrastructure and learning facilities needed by lecturers to maintain learning quality.
Keywords: 650; academic interest; academic performance; learning attitude; learning quality